Sustainable rural livelihoods - Carney, Diana (ed.) (London, 1998)
The aim of this book is to wides the debate around the UK Department for International Development's commitment to myyeting minable al filo The influided ofhapters papers which were ed as a confirmes on dhe jet July 1998 for able mutual resource speciall egies bed and of Ballitond comesinis and mund operationallied with peers. This volume represents a vieting guine for drinking about the new golloy desetion and the opportunities in prevents.
Keywords: Sustainable development